PENERAPAN METODE MATRIX TRANSPORTASI BOWMAN UNTUK MEMINIMUMKAN BIAYA PADA PERENCANAAN PRODUKSI - Paudi, Rivka; Nurwan, Nurwan; Payu, Muhammad Rezky Friesta (Department of Mathematics Education, Universitas Kuningan, 2023)
Istana Coklat Bakery, one of the bread industries in Gorontalo, produces two types of products, namely birthday cake and cake. Production planning in the istana Coklat Bakery begins with forecasting demand using double moving average method to production cost data, and production costs as variables that will be counted in the Bowman Transportation Matrix. based on the research results, obtained that the production process was fulfilled for regular production and overtime production using the Bowman Transportation Matrix method. The total cost obtained from production planning using the Bowman transportation matriks method is IDR 864,437,500.